2017
DOI: 10.1111/iej.12846
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fatigue resistance of R‐Pilot, HyFlex EDM and PathFile nickel‐titanium glide path files in artificial canals with double (S‐shaped) curvature

Abstract: R-Pilot NiTi glide path files, used in a reciprocating motion, had the greatest cyclic fatigue resistance amongst the tested NiTi glide path files in an artificial S-shaped canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 24 publications
2
51
2
5
Order By: Relevance
“…Uslu et al . () recently reported that the cyclic fatigue resistance of R‐Pilot files was significantly higher than that of HyFlex EDM and PathFile instruments. The authors attributed these results to the reciprocating motion with which the R‐pilot files are used, rather than the continuous rotary motion of HyFlex EDM and PathFile instruments.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Uslu et al . () recently reported that the cyclic fatigue resistance of R‐Pilot files was significantly higher than that of HyFlex EDM and PathFile instruments. The authors attributed these results to the reciprocating motion with which the R‐pilot files are used, rather than the continuous rotary motion of HyFlex EDM and PathFile instruments.…”
Section: Discussionmentioning
confidence: 94%
“…Considering that the alloy and kinematic characteristics of WOG and Reciproc files are similar to those of WOG Glider and R-Pilot files, respectively, the greater time to fracture values of R-Pilot might be related to the design of the files and the smaller horizontal cross-sectional area than WOG Glider measured in the SEM images. Uslu et al (2018) recently reported that the cyclic fatigue resistance of R-Pilot files was significantly higher than that of HyFlex EDM and PathFile instruments. The authors attributed these results to the reciprocating motion with which the R-pilot files are used, rather than the continuous rotary motion of HyFlex EDM and PathFile instruments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the contrary, Uslu et al . () concluded that a file with controlled memory (HyFlex EDM; Coltène Whaledent, Altstätten, Switzerland) exhibited lower cyclic fatigue resistance than a file made of M‐wire alloy (R‐PILOT) in an artificial S‐shaped canal.…”
Section: Discussionmentioning
confidence: 99%
“…Engine-driven instruments, specifically designed for glide path preparation, have been developed (Paleker & van der Vyver 2016, Uslu et al 2018. Recently, glide path systems, using reciprocation motion, such as the WaveOne Gold Glider (Dentsply Sirona, Ballaigues, Switzerland) and R-PILOT (VDW GmbH, Munich, Germany), were launched.…”
Section: Introductionmentioning
confidence: 99%